EVALOE-DSS as a self-assessment and decision-making tool on the teaching of oral language in a school context: results of a pilot study - Marta Gràcia; Laura Amado; Sonia Jarque; Daniela Bitencourt; Fàtima Vega; Carles Riba (Ignatianum University Press, 2019)
School is a natural context for development in which the communicative strategies used by teachers when interacting with students are essential for the development of communicative and linguistic competence. The objective of this study was to construct, implement and validate a first version of a self-assessment and decision-making tool on the teaching of oral language at school. It is an adaptation of the Oral Language Assessment in the School Context Scale (Escala de Valoración de la enseñanza de la Lengua Oral en contexto Escolar-EVALOE) (Gràcia et al., 2015) based on the use of the Conversational Methodology. This is a multiple case study focusing on four teachers (1 from an ordinary school, 2 from a rural school and 1 from a special education school). For six months, the teachers self-assessed their teaching practices with the tool, made decisions to improve it, and introduced changes in their classes. The researchers observed five class sessions of each teacher, assessed them with the same tool and each teacher-researcher pair conversed and reflected on the classes in five meetings throughout the semester. The results show that, in spite of the fact that there were important differences between teachers, the EVALOE - Decision Support System (EVALOE-SSD) is a useful tool that facilitates self-assessment, decision-making and the introduction of changes in the classes in order to promote the development of communicative and linguistic competence in the students. The analysis identified elements that can be improved and that will be considered during the review of the tool.